Research of hieroglyphic signs using audiovisual digital analysis methods - Egorova, Maia A.; Egorov, Alexander A. (Discrete and continuous models and applied computational science, 2025)
A study of ancient written texts and signs showed that the hieroglyphs and structure of the archaic sentence have much in common with the modern Chinese language. In the context of the history and evolution of the Chinese language, its characteristic tonality and melody are emphasized. The main focus of the work is on the study of the sound properties of hieroglyphs (keys / Chinese radicals) found simultaneously in ancient inscriptions as well as in modern text messages. The article uses modern digital methods of sound analysis with their simultaneous visualization. To characterize the sound of hieroglyphs (in accordance with the Pinyin phonetic transcription adopted in China), two (FI, FII), three (FI, FII, FIII) or four (FS, FI, FII, FIII) formants are used, which create a characteristic F-pattern. Our proposed model of four formants for typical hieroglyphs is called the basic one “F-model”, it’s new and original. To visualize the formants, digital audio signal processing programs were used. The data obtained were compared with the corresponding spectrograms for Mandarin (standard) Chinese. Their correspondence to each other has been established. When analyzing F-patterns, an original model was used, which made it possible to characterize spectrograms in the frequency and time domains. The formalized description of basic components of basic “F-model” of a pronunciation of hieroglyphs is given. In conclusion, several areas are noted in which the use of various methods of audiovisual research is promising: advanced innovative technologies (artificial intelligence and virtual reality); television, theatrical video production; evaluation of the quality of audiovisual content; educational process. The present study has shown that described promising research methods can be useful in analyzing similar ancient hieroglyphs.